Pengaruh Penambahan Cangkang Telur Terhadap Daya Dukung Tanah Lempung - Florence Haumahu; Sjafrudin Latar; Nexsien R. Maitimu (Universitas Darul Ulum Islamic Centre Sudirman GUPPI, 2026)
This study aims to determine the effect of adding eggshell powder on the bearing capacity of clay soil in Dusun Ahuru, Ambon. Clay soil is know for high plasticity and low bearing capacity. Stabilization was carried out with variations of eggshell powder 5%, 10% and 15% with varying incubation periods of 0, 7, and 14 days. Laboratory test included physica properties and California Bearing Ratio (CBR). Results showed that the addition of 15% eggshell powder with a curing 14 days significantly increased the CBR value from 2,15% (original soil) to 10,42% The calcium carbonate in eggshell powder reacted with clay soil, thereby improving the mechanical properties.